Prophylaxis of Macular Edema with Preoperative Intravitreal Bevacizumab in Patients with Diabetic Retinopathy Undergoing Phacoemulsification - Muhammad Abid Javed, Sidrah Latif, Rana Muhammad Mohsin Javaid, Asad Aslam Khan, Tehseen Mahmood Mahju, Farooq Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: To determine frequency of post-operative macular edema in diabetic retinopathy patients having received preoperative intravitreal bevacizumab, after phacoemulsification cataract surgery while compared with the controls. Study Design: Quasi experimental trial Place and Duration of Study: Department of ophthalmology eye unit 3, KEMU /Mayo hospital, Lahore from March 2020 to August 2020. Methods: A total of 60 patients were included in the study and randomly divided into two groups. Patients of study group were given 1.25mg bevacizumab injection by IV (intravitreal) in route two weeks prior to surgery while nothing was administered in the control group. Before one week of surgery ocular examination and OCT were performed and it was repeated after every month of performance of surgery. Allocation of patients was even not known to the researcher to avoid biasness. Components of monthly examination were best correct visual acuity, slit lamp examination and central macular thickness quantification with OCT. Standard cataract surgery was performed in all the patients (phacoemulsification and implantation of monofocal intraocular lens (IOL). Post-operatively, all patients were given standard treatment i.e moxifloxacin-dexamethasone). Follow up of all the patients was made for consecutive three months on monthly basis to assess outcome variables i.e macular edema was observed keeping in view central macular thickness. Results: In patients of study group, 16.66% had developed macular edema while in control group it was observed in 46% patients. While comparing macular edema between side of eye, study group had 02 (13.33%) patients belonging to right eye while 03(20.0%) had left eye. However, in control group it was 08 (53.33%) and 06 (40.0%) for right and left eyes respectively. Group A had 230.23 ± 32.16 µm central macular thickness while it was 274.21 ± 25.34 µm in group B. Conclusion: In macular edema prophylaxis, using preoperative intravitreal bevacizumab is efficacious in comparison with the controls in patients with mild-moderate NPDR with macular edema. Keywords: NPDR, Macular edema, Intravitreal Bevacizumab, Phacoemulsification Surgery, Diabetic Retinopathy.